Hand Eczema among General Population in the time of Enhanced Hand Hygiene during COVID-19 Pandemic - Salim Ali Algaadi, (Pakistan Journal of Medical & Health Sciences, 2022)
During the COVID-19 pandemic, health authorities in most of the world recommend people maintain hand hygiene to prevent the spread of the virus. Unfortunately, this has resulted in an increased number of hand dermatitis among health care workers (HCW) and the general population. Hand eczema results from the damage to the epidermal barrier that induces inflammation and activates the innate immune system. In this brief study, we assess hand eczema prevalence during the Covid-19 pandemic in the general population of Saudi Arabia via a self-administered online questionnaire. The total number of participants was 502, of which 268 (53.4%) were males. Most participants were younger than 30 years (67.9%), while only (2.2%) were older than 60 years. Forty percent of participants developed new-onset hand skin damage during the pandemic, and this was proportionally correlated with the daily average frequency of handwashing with soap and water. We hope this brief study paves the way for further larger epidemiological studies.